Salinity Stress and Calcium in Pomegranate: Impacts on Growth, Ion Homeostasis, and Photosynthesis - Christos Chatzissavvidis; Nina Devetzi; Chrysovalantou Antonopoulou; Ioannis E. Papadakis; Ioannis Therios; Stefanos Koundouras (Horticulturae)
Salinity has significant impacts on crops, a problem that is exacerbated under climate change conditions. For this reason, research is focused on possible ways to mitigate the impacts by adapting cultivation methods such as administering appropriate materials or formulations to plants. Therefore, this study investigated the effects of calcium (Ca2+) supplementation on the growth, physiology, and chemical composition of pomegranate plants (Punica granatum L. cv. ‘Wonderful’) grown under salinity stress. Young self-rooted plants were cultivated in pots containing a sand/perlite (1:1) mixture and irrigated with Hoagland’s nutrient solution amended with NaCl (0, 60, or 120 mM) and CaCl2·2H2O (0 or 10 mM). Salinity significantly reduced the fresh and dry weight of aboveground tissues; photosynthetic performance; chlorophyll content; and potassium (K), calcium (Ca), and magnesium (Mg) concentrations, particularly under high NaCl levels. Sodium (Na) accumulation increased in all plant parts, while nitrogen (N), manganese (Mn), and zinc (Zn) concentrations were elevated in basal leaves. Calcium supplementation mitigated several of these adverse effects, especially under moderate salinity. It helped maintain leaf biomass, supported K+ retention in roots, partially improved chlorophyll concentration, and limited Na+ accumulation in certain tissues. However, Ca2+ application did not consistently reverse the negative impacts of severe salinity (120 mM NaCl), and in some cases, interactions between Ca2+ and other nutrients such as Mg2+ were antagonistic. These findings confirm the inherent salt tolerance of pomegranate and demonstrate that calcium plays a partially protective role under salinity, particularly at moderate stress levels. Further research is needed to optimize Ca2+ use in saline agriculture and enhance sustainable cultivation of pomegranate in salt-affected soils.